Multi-Scale Influence of Flexible Submerged Aquatic Vegetation (SAV) on Estuarine Hydrodynamics - Elizabeth R. Holzenthal; David F. Hill; Meagan E. Wengrove (Journal of Marine Science and Engineering, 2022)
Bottom friction is an important process in coastal and estuarine environments because it can reduce wave heights and moderate tidal currents. When modeling large systems with spatially varying hydraulic properties, bottom friction values are commonly derived from land use classification products. However, estimation of bottom friction for vegetated areas can be more challenging due to the complicated and time-varying geometry of the roughness elements. This is particularly true of flexible, buoyant submerged aquatic vegetation (SAV) species, such as seagrasses and kelps, that deform under waves and currents. In this study we incorporate a dynamic friction model that includes the temporal variation in SAV drag forces into a depth-integrated coupled circulation-wave model. In vegetated areas, the bottom friction is continuously updated based on plant geometry, water depth, and combined wave-current velocities. Taking a multi-scale approach, we use the model to investigate the impact of SAV dynamics on both the localized and the integrated bay-wide hydrodynamics of a riverine and tidally influenced estuary. First, we investigate SAV modification of velocity fields and its implications for sediment transport and circulation pathways. Then, we show how SAV can modify tidal behavior throughout the estuary.